Upaya Mengatasi Kebocoran Penerimaan Retribusi Angkutan Umum: Studi Angkutan Umum Plat Hitam dan Plat Kuning - Toyyibatun Nisa’ Alawiyah; Agus Sugiono (Universitas Nusantara PGRI Kediri, 2022)
This research aims to find out dishub's efforts in overcoming leaks of public transport levy receipts. The object of the research is the Pamekasan District Transportation Office, especially Pademawu Pamekasan Old Terminal. Types of qualitative research with Primary data sources and Secondary data. Data obtained from interviews and observations. The results of the study concluded that dishub efforts in overcoming leakage of public transportation levy receipts through several steps, namely the first: The Department of Transportation conducts direct delivery of officers to the field to prevent public transportation of black plates, Second: The Department of Transportation seeks to implement a deposit payment system directly through the regional bank that has been determined by the local government of Pamekasan Regency, Third: Perform repoltal installation, and conduct joint operations (raids) with the police that are held 3 times a year, as well as conduct direct and indirect supervision. However, there is a deficiency in the receipt of the levy that is not yet eligible from the levy withdrawal procedure because the ticket expenditure is not in accordance with the receipt of the levy specified (Regional Regulation No.14 of 2014 on terminal levy).